Irony as a Mechanism for Critiquing Pragmatic Theories - Singh, Raj Kishor (Nepalese Linguistics, 2024)
This paper explores the role of irony as a powerful mechanism for critiquing key pragmatic theories, including Austin’s Speech Act Theory, Grice’s Cooperative Principle, Leech’s Politeness Principle, and Wilson and Sperber’s Relevance Theory. While these theories provide robust frameworks for understanding the dynamics of language use, they often assume a level of straightforwardness and sincerity in communication that irony subverts. Through an analysis of literary quotations, this study demonstrates how irony disrupts the expected norms of speech acts, cooperative communication, politeness, and relevance, revealing the limitations and oversights inherent in these pragmatic models.